The Role of the Sharing Economy Model in the Development of the Smart City Concept: A Critical Literature Review - Anna Irena SZYMANSKA (Communications of International Proceedings, 2024)
The concept of the sharing economy, aligning with the third generation of smart cities (smart city 3.0), termed the sharing smart city, has become a fundamental instrument in the creation of intelligent urban environments. However, there remains a lack of a cohesive global discourse on the sharing smart city, as well as a clear, standardized definition of the concept. This contributes to a wide range of interpretations regarding what constitutes a sharing smart city and the appropriate methods for its implementation. This publication adopts a descriptive approach, with its primary objective being to substantiate the potential of the sharing economy in driving the development of smart cities. The analysis was conducted through a critical review of the relevant academic literature. The literature database was developed using two international, interdisciplinary electronic bibliographic databases: Web of Science and Scopus. The analysis of the selected articles resulted in their classification into four primary categories: A, B, C, and D. The study demonstrated that scholarly interest in the impact of the sharing economy on the transformation and development of smart cities is a relatively nascent research area, emerging primarily in the last decade of the 21st century. As a result of the analysis, five key thematic areas were identified. Additionally, an attempt was made to define the concept of the sharing smart city and to develop a conceptual model. It has also been demonstrated that both concepts - the sharing economy and smart city - intersect in areas such as creative community, digital technologies, and sustainable development.
Keywords: smart city; sharing economy; sharing smart city; sustainable development